PROGRAM BIMBINGAN DAN KONSELING DENGAN TEKNIK COMMUNITY-BASED PARTICIPATORY RESEARCH (CBPR) UNTUK MENINGKATKAN KESEHATAN MENTAL WARGA BINAAN DI LAPAS KELAS III RANGKASBITUNG - Rafli Hibatullah; Arga Satrio Prabowo; Lenny Wahyuningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Mental health is a crucial aspect of the rehabilitation process for correctional inmates, considering that the prison environment may contribute to psychological distress such as stress, anxiety, and depression. This study aims to examine the effectiveness of a guidance and counseling program based on the Community-Based Participatory Research (CBPR) approach in improving the mental health of inmates at Class III Rangkasbitung Correctional Facility. The research employed a CBPR approach by actively involving researchers, correctional officers, and inmates in the stages of problem identification, program planning, implementation, and evaluation. The research subjects were inmates of Class III Rangkasbitung Correctional Facility, and psychological conditions were measured using the Depression Anxiety Stress Scale-21 (DASS-21) through pretest and posttest assessments. The results indicate a reduction in levels of stress, anxiety, and depression among inmates after participating in the guidance and counseling services. At the posttest stage, all respondents were classified within the normal and mild categories across the three psychological dimensions. These findings demonstrate that CBPR-based guidance and counseling services are effective in helping inmates manage psychological distress and improve mental well-being. Furthermore, the participatory nature of the CBPR approach enhances the relevance and sustainability of rehabilitation programs. Therefore, this program can serve as an alternative model for developing mental health services in correctional institutions in line with the objectives of the correctional system.